Unaveraged simulations of a cavity based free electron laser - Pornthep Pongchalee; Brian W.J. McNeil (Results in Physics, 2024)
The computer simulation of a cavity-based (oscillator) Free-Electron Laser (FEL) requires the modelling of both the electron-light interaction in the FEL undulator and the radiation propagation within the optical cavity. The unaveraged 3D FEL simulation code Puffin has been coupled with the Optical Propagation Code (OPC) to allow a broadband, high temporal-resolution cavity FEL to be modelled for the first time. This requires the translation of the radiation field formats between the Puffin and OPC codes. This translation is described and the coupled codes are then used to model an example of a Regenerative Amplifier FEL operating in the VUV.